Penerapan Tri Hita Karana dalam Perancangan, Pembangunan serta Operasi dan Pemeliharaan Jaringan Irigasi Subak - Wisnu Wardana; Putu Sudira (agriTECH, 1999)
Subak is a specific irrigation scheme in Bali that has been established since centuries ago. The long life of Subak in favor of specific way of life called Tri Karam. People there believe that they will be happy if they can make a harmony among three principles of Tri Hua Karana - Parhyangan (divineness to the God), Pawongan (human being), and Palemahan (nature) in their life. This study describes an application of Tri Him Karana in design, construction, operation and maintenance of subak irrigation scheme. Result shows that Tri. Hita Karana has been applied. Parhyangan principles is used in every activitiy that refers to Sang Hyang Widi Wasa for blessing them. The application of Pawongan principle is appreciated to all human being activities. While, Palemahan principle is done by taking care of nature conservation by people.